Linkages Between Global Capital Flows, Stock Market, and Monetary Policy : Evidences from India - Pathak, Taral (Indian Journal of Finance, 2018)
Globalization set into motion financial liberalization of economies, which led to integration of financial markets globally, resulting in global capital flows (GCFs) from developed economies to emerging market economies (EMEs). 'Push' factors were seen as the reason for capital flows to an economy and found a high proportion of synchronization of GCFs across financial markets, well-exemplified in the asset bubble (AB) formation, and financial crisis of 2008 (Ghosh, Qureshi, Kim, & Zalduendo, 2014). The role of financial linkages and transmission channels in the spread of the crisis was examined by Blanchard, Dell'Ariccia, and Mauro (2010) and Dungey, Osborn, and Raghvan (2013). In India, RBI manages the impact of GCFs on the economy and its effectiveness depends upon the efficacy of the transmission channel, especially the asset price and credit channel. Therefore, conditional to an efficient transmission channel, should the RBI contemplate an interest rate response to contain plunging asset prices during an AB formation, making it imperative to investigate the working and effectiveness of the asset price channel in India. The current paper scientifically probed this question, 'Can the RBI manage asset prices in the event of a bubble?' The study used monthly time series data of various variables of BSE from January 2004 - 2013 and checked the causality between them. Results established causality between GCFs to India and BSE turnover with a 2-month lag. Results of pairwise Granger causality concluded that repo rate Granger caused BSE Sensex returns with a 3-month lag, which is relatively a long-lag, if RBI wants the mechanism to work during a crisis situation. The credit channel was most sluggish (32-month lag), implying that if RBI slashed interest rates to increase availability of credit in the market, then its move might not be impactful as banks might not pass on the cut to the customers/real economy.